2020
DOI: 10.1538/expanim.19-0072
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fish and mealworm larvae meals as alternative dietary protein sources on nutrient digestibility and gastrointestinal function in <i>Chinchilla lanigera</i>

Abstract: Chinchillas are herbivores, but wild chinchillas may occasionally consume animal-based foods. The aim of this study was to determine the effect of fish meal (FM) and mealworm meal (MWM) included in complete pelleted diets on nutrient digestibility and gastrointestinal function in chinchillas. The experiment was performed on 24 male, divided into three groups, n=8. Control group (C) was fed a diet containing 10% soybean meal (SBM). In the experimental group FM, chinchillas received a diet containing 3% fish mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
3
6
1
Order By: Relevance
“…The gut morphometric index and organ histopathology were not affected by the addition of house fly and mealworm fat diets. Similar results were reported by Gugołek et al [54] who showed supplementation of fish meal and mealworm MW meal had no considerable variation in the digestibilitiesdigestibility of DM, organic matterOM, total energy, total protein, and NDF between the treatments and the control 서식 있음: 글꼴: 굵게, 기울임꼴 없음…”
Section: Mealworm Larvae Effect On Nutrient Digestibility In Ruminantssupporting
confidence: 86%
See 1 more Smart Citation
“…The gut morphometric index and organ histopathology were not affected by the addition of house fly and mealworm fat diets. Similar results were reported by Gugołek et al [54] who showed supplementation of fish meal and mealworm MW meal had no considerable variation in the digestibilitiesdigestibility of DM, organic matterOM, total energy, total protein, and NDF between the treatments and the control 서식 있음: 글꼴: 굵게, 기울임꼴 없음…”
Section: Mealworm Larvae Effect On Nutrient Digestibility In Ruminantssupporting
confidence: 86%
“…group. However, it should be noted that total protein digestion was higher in groups control and mealworm than in the fish meal group [54]. An enzymatic method was used to analyze total protein digestibility of Tenebrio molitor and Hermetia illucens in-vitro digestion experiment.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…Human vision has natural limitations. In some application scenarios, machine vision has advantages over human physiological vision, which is more accurate, objective, and stable [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The activity of the above enzymes is associated with important physiological processes such as starch hydrolysis (α-glucosidase), hydrolysis of non-starch polysaccharides (NSPs) and degradation of cellulose (β-glucosidase), utilization of raffinose-family oligosaccharides (α-galactosidase), degradation of NSPs present in both cereals and protein sources used in this study, namely arabinans containing terminal arabinofuranoses as well as internal arabinopyranoses (both arabinosidases) [ 38 , 39 ]. It should be noted that similar increasing and decreasing trends in bacterial enzyme activity in the colonic digesta, induced by dietary supplementation with 4% mealworm larvae meal, were observed in chinchillas [ 29 ].…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, the administered feed contained only 0.12% chitin. In a study of another herbivorous species, the chinchilla, diets supplemented with 4% dried mealworm (Tenebrio molitor ) larvae meal had no influence on the digestibility of DM, organic matter, total protein, NDF and energy, but they improved the digestibility of ether extract, ADF and ADL [ 29 ]. Martins et al [ 30 ] and Gasco et al [ 26 ] found that black soldier fly ( Hermetia illucens L.) larvae fat and mealworm fat had no adverse effects on nutrient digestibility in rabbits.…”
Section: Discussionmentioning
confidence: 99%